Bioinformatic Analysis of the Effect of the Sirtuin Family on Differentiated Thyroid Carcinoma. (30th January 2022) - Yao, Lijun; Wang, Yinhua
Abstract : A growing body of experimental evidence suggests that sirtuins ( SIRTs ) are associated with tumorigenesis in differentiated thyroid cancer (DTC). Nevertheless, the involvement of SIRTs in the pathogenesis of DTC and their clinical value remain ill-defined and should be thoroughly examined. We explored the transcription of SIRTs and survival data of patients with DTC by the systematic utilization of bioinformatics to analyze data of publicly accessible databases including Oncomine, cBioPortal, Kaplan-Meier Plotter, Gene Expression Profiling Interactive Analysis (GEPIA), Protein Atlas, LinkedOmics, and GSCALite. The examination of gene expression profiles showed that SIRT2, SIRT3, SIRT4, SIRT5, and SIRT6 were downregulated in DTC tissues compared with the normal thyroid tissues. The decreased expression levels of SIRT2, SIRT4, and SIRT5 were correlated with advanced tumor stages. The survival results showed that the increased SIRT4 mRNA expression level was associated with improved overall survival (OS) in the DTC patients. In addition, patients with DTC with high SIRT2, SIRT3, SIRT4, and SIRT5 mRNA levels had higher disease-free survival (DFS). These results showed that SIRT2, SIRT3, SIRT4, SIRT5, and SIRT6 are potential targets for precise treatment of DTC patients and that SIRT2, SIRT3, SIRT4, and SIRT5 are novel potential biomarkers for the prognosis of DTC.